In Vivo Antimalarial Activity of the Leaf Extract of Osyris quadripartita Salzm. ex Decne and Its Major Compound (–) Catechin - Teyiba Kemal; Kebede Feyisa; Daniel Bisrat; Kaleab Asres (Journal of Tropical Medicine)
Background. The leaves of Osyris quadripartita Salzm. ex Decne, endemic to Ethiopia, are traditionally used for the treatment of malaria. Previous phytochemical investigations of Osyris species showed the presence of flavonoids, anthracene derivatives, and sesquiterpene lactones as the main constituents. The aim of the present study was to investigate the antimalarial activity of the leaf extract of O. quadripartita and its isolated constituent against mice infected with Plasmodium berghei. Methods. Isolation of a compound was carried out on silica gel column chromatography of the extract eluting with gradient mixtures of CHCl3/MeOH. Structural elucidation of the isolated compound was achieved by ESI-MS and 1D-and 2D-NMR spectral data. Peter’s 4-day suppressive test method was used to determine the antimalarial activity of the test substances. Level of parasitemia, survival time, and body weight change were used to determine the antimalarial activity of the test substances. Results. (–) Catechin was isolated and characterized from the hydroalcoholic extract of O. quadripartita. At a concentration of 400 mg/kg, both the extract and (–) catechin exhibited antimalarial activity with the highest chemosuppression values of 70.61% and 64.26%, respectively. Conclusion. These findings indicate that O. quadripartita is endowed with genuine antimalarial activity attributed in part, to its (–) catechin content. Hence, the present study may validate the traditional use of the plant for the treatment of malaria.